Hydrology and public health: linking human leptospirosis and local hydrological dynamics in Trinidad, West Indies - Vega-Corredor, Maria C; Opadeyi, Jacob (My University, 2014)
Abstract Background Human leptospirosis is currently one of the most widespread bacterial zoonoses and is the only epidemic-prone infection that can be transmitted directly from contaminated water. Transmission in humans is caused by direct or indirect contact with contaminated water, soil or infected urine, blood or tissue of carrier animals. Initial symptoms are similar with those suffered during influenza, dengue or viral hepatitis. As the disease progresses, internal organs can be compromised causing severe hemorrhages, organ failure and, potentially, death. Human leptospirosis is a growing global public health problem although, in endemic areas, it is considered a neglected disease. Hydrological factors, including rainfall and floods, have been frequently related to human leptospirosis. In the Caribbean, leptospirosis is endemic and it is a disease under surveillance. Based on confirmed cases, in Trinidad andamp; Tobago the average annual incidence of human leptospirosis ranges between 1.78 to 1.84 cases per 100,000 population. Methods In this paper, we used Geographical Information System (GIS) analysis and Geographically Weighted Poisson Regression (GWPR) for the development of ecological models, to assess the spatial variability in the relationships between local hydrological factors and human leptospirosis occurrence at the community level on the island of Trinidad. Five explanatory covariates were developed for the analysis: rainfall, river drainage density, proportion of soil with free drainage, proportion of soil with imperfect/impeded drainage, and a topographic wetness index. Results The GWPR model presented an improvement (AICcand#8201;=and#8201;392.46; devianceand#8201;=and#8201;583.36) over the Global regression model (AICcand#8201;=and#8201;595.52; devianceand#8201;=and#8201;381.78), indicating spatial variability in the relationship of human leptospirosis and hydrological factors. Pseudo t-values of rainfall, imperfect/impeded drainage soil and the topographic wetness index showed high values (|t| andgt;1.96) indicating that local relationships with leptospirosis occurrence may be significant. Conclusion Results suggest that rainfall, imperfect/impeded drainage soil and topographic wetness index influence the local dynamics of human leptospirosis.